A retrospective analysis of High-Dose Interleukin-2 (HD IL-2) following Ipilimumab in metastatic melanoma. Issue 1 (20th September 2016) - Buchbinder, Elizabeth I.; Gunturi, Anasuya; Perritt, Jessica; Dutcher, Janice; Aung, Sandra; Kaufman, Howard L.; Ernstoff, Marc S.; Miletello, Girald P.; Curti, Brendan D.; Daniels, Gregory A.; Patel, Sapna P.; Kirkwood, John M.; et al.
Abstract : Background: High dose interleukin-2 (HD IL-2) can induce durable responses in a subset of patients leading to long-term survival. Immune checkpoint blockade (ICB) has demonstrated similarly durable responses in a larger proportion of patients. However, not all patients respond to immune checkpoint blockade and subsequent therapeutic options need to be explored. Methods: The PROCLAIM database was queried for patients with metastatic melanoma who had received HD IL-2 after treatment with ipilimumab or without prior ICB. Patient characteristics, toxicity and efficacy were analyzed. Results: A total of 52 metastatic melanoma patients were treated with high dose IL-2 after ipilimumab and 276 patients were treated with high dose IL-2 without prior ICB. The overall response rate in the prior ipilimumab group was 21 % as compared to 12 % in the group that had not received prior ipilimumab. The median overall survival, measured from the initiation of HD IL-2 therapy, was 19.3 months in the prior ipilimumab group and 19.4 months in the no prior ICB group. Toxicities observed on HD IL-2 were relatively equivalent between the groups although there were cases of CTLA4 antibody-induced colitis reported after HD IL-2 treatment and a CTLA4 antibody-induced colitis related death. Conclusion: In this retrospective analysis HD IL-2 therapy displayed antitumor activity in melanoma patients who progressed following treatment with ipilimumab. Most HD IL-2 toxicity was not worsened by prior ipilimumab therapy except for one treatment related death from colitis. Care should be taken to avoid reactivation of CTLA4 antibody-induced colitis.